Family history of later-onset breast cancer, breast healthy behavior and invasive breast cancer among postmenopausal women: a cohort study - Gramling, Robert (BioMed Central, 2010)
INTRODUCTION: A family history of later-onset breast cancer (FHLBC) may suggest multi-factorial inheritance of breast cancer risk, including unhealthy lifestyle behaviors that may be shared within families. We assessed whether adherence to lifestyle behaviors recommended for breast cancer prevention--including maintaining a healthful body weight, being physically active and limiting alcohol intake--modifies breast cancer risk attributed to FHLBC in postmenopausal women. METHODS: Breast cancer outcomes through August 2003 were analyzed in relationship to lifestyle and risk factors collected by questionnaire during enrollment (between 1993 and 1998) of 85,644 postmenopausal women into the Women's Health Initiative Observational Study. RESULTS: During a mean follow-up of 5.4 years, 1997 women were diagnosed with invasive breast cancer. The rate of invasive breast cancer among women with an FHLBC who participated in all three behaviors was 5.94 per 1,000 woman-years, compared with 6.97 per 1,000 woman-years among women who participated in none of the behaviors. The rate among women with no FHLBC who participated in all three behavioral conditions was 3.51 per 1,000 woman-years compared to 4.67 per 1,000 woman-years for those who participated in none. We did not observe a clinically important departure from additive effects (Interaction Contrast: 0.00014; 95% CI: -0.00359, 0.00388). CONCLUSIONS: Participating in breast healthy behaviors was beneficial to postmenopausal women and the degree of this benefit was the same for women with and without an FHLBC.